Job Satisfaction and Work Stress Associated With Burnout in Shadow Teachers: Kepuasan Kerja dan Stres Kerja yang Berkaitan dengan Burnout pada Guru Bayangan - Silvi Jihan Amalia; Eko Hardi Ansyah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Burnout is a psychological condition characterized by emotional exhaustion, depersonalization, and reduced personal accomplishment arising from prolonged occupational stress, particularly in demanding educational environments. Specific Background: In inclusive education settings, shadow teachers play a crucial role in assisting students with special needs, requiring sustained emotional engagement, patience, and instructional adaptation, which may increase vulnerability to occupational strain. Knowledge Gap: Despite growing attention to teacher well-being, empirical studies examining job satisfaction and work stress simultaneously as predictors of burnout among shadow teachers remain limited. Aims: This study aimed to examine the relationships between job satisfaction and work stress with burnout among shadow teachers in Sidoarjo. Results: Using a quantitative design, data were collected from 186 shadow teachers selected through purposive sampling from a population of 400 individuals. Psychological instruments included the Job Satisfaction Survey, Job Stress Scale, and Maslach Burnout Inventory–Educators Survey (MBI-ES). Multiple linear regression analysis conducted using JASP version 0.16.4 indicated a statistically significant relationship between job satisfaction and work stress with burnout (p = 0.001 < 0.05). Novelty: The study provides empirical evidence integrating job satisfaction and work stress variables within a single regression model focusing specifically on shadow teachers in inclusive education contexts. Implications: The findings highlight the importance of considering occupational conditions and psychological factors in understanding burnout among educational support professionals, supporting future organizational and educational strategies addressing teacher well-being. Highlights: Statistical Testing Confirmed a Significant Simultaneous Relationship Among Measured Variables. Regression Modeling Identified Occupational and Psychological Factors Linked to Emotional Exhaustion Conditions. Data From 186 Educational Assistants Provided Empirical Evidence Within Inclusive Learning Settings. Keywords: Job Satisfaction, Work Stress, Burnout, Shadow Teachers, Inclusive Education